преобразуйте в многочлен (Смотрите вложение)
раскроем скобки х^3 -6х^2 -36х-6х^2+36+216 - 2*(х^2 -6х-9) = = х^3 -12х-36х+36х+216-4х^2 -12х +18 = = x^3-2x^2+234=x^2(x-2)+234
(x+6)(x²-6x+36)-2(x-3)(x+3)=x³+216-2(x²-9)=x³+216-2x²+18=x³-2x²+234
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
раскроем скобки
х^3 -6х^2 -36х-6х^2+36+216 - 2*(х^2 -6х-9) =
= х^3 -12х-36х+36х+216-4х^2 -12х +18 =
= x^3-2x^2+234=x^2(x-2)+234
Verified answer
(x+6)(x²-6x+36)-2(x-3)(x+3)=x³+216-2(x²-9)=x³+216-2x²+18=x³-2x²+234